The Impact of Public Employment: Evidence from Bonn - Sascha Becker; Stephan Heblich; Daniel Sturm (European Regional Science Association (ERSA), 2013)
This paper evaluates the impact of relocations of public employment across cities on private sector activity. To identify the effect of changes in public employment on the private sector, we exploit the relocation of the German Federal Government from Berlin to Bonn in the wake of the Second Word War as a source of exogenous variation. In line with the predictions of a standard economic geography model we ...nd that an increase in public employment puts downward pressure on private sector employment. We provide evidence that this negative impact is driven by changes in wages and rents which are consistent with the mechanisms of the model.
Keywords: 330; Public Employment; Crowding Out; Economic Geography; German Division